2011
DOI: 10.1007/s13224-011-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of Endometrial Pathology in Abnormal Uterine Bleeding

Abstract: There is an age specific association of endometrial lesions. In perimenopausal women AUB is most commonly dysfunctional in origin and in reproductive age group, one should first rule out complications of pregnancy. The incidence of disordered proliferative pattern was significantly high in this study, suggesting an early presentation of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

46
120
8
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(177 citation statements)
references
References 10 publications
46
120
8
3
Order By: Relevance
“…It is thought to be due to anatomic vascular variations or local abnormal defective haemostatic mechanisms. 12 In this study, endometrial carcinoma was found in 2 (1.11%) cases, which is almost similar to that reported by Khan S et al and Jairajpuri ZS et al 17 In the present study, endometrial carcinoma was found in ˃ 50 years of age group. A study done by Dangal et al in Nepal documented a lower incidence of endometrial cancer in Nepalese woman attributing it to the practice of early childbearing and multiparty.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is thought to be due to anatomic vascular variations or local abnormal defective haemostatic mechanisms. 12 In this study, endometrial carcinoma was found in 2 (1.11%) cases, which is almost similar to that reported by Khan S et al and Jairajpuri ZS et al 17 In the present study, endometrial carcinoma was found in ˃ 50 years of age group. A study done by Dangal et al in Nepal documented a lower incidence of endometrial cancer in Nepalese woman attributing it to the practice of early childbearing and multiparty.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, simple hyperplasia was predominant which was similar to the study of Doraiswami S et al who observed 68% incidence of endometrial hyperplasia in 40-49 years of age group. 12 Endometrial hyperplasia is commonly seen in perimenopausal age group due to failure of ovulation. Persistent unriped follicles expose the endometrium to excessive and prolonged estrogenic action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, study done by Doraiswamy et al also showed that polyps accounted for 11.2% cases of AUB. 13 The histopathology of endometrium showed proliferative phase which indicates that their growth is estrogen regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies, it is more common in the 41-50 age group. 15,[18][19] Diagnosing the patients at the earliest stage of this spectrum will be of definitive help to the practicing gynaecologists to prevent the disease progression.…”
Section: Functional Causesof Aubmentioning
confidence: 99%